Evaluating Green Entrepreneuri AL Mindset Shifts In High School Youths: Case Of SMA Yaspen Tugu Ibu - Depok - Laili Savitri Noor; eka sudarmaji; Sri Ambarwati; Sri Widyastuti; Bayu Retno; Ateniyanti Ateniyanti; Herlan Masrio; Muhammad Rubiul Yatim; Rika Kaniati; Athia Zerlina (SULUH: Jurnal Abdimas, 2024)
Green entrepreneurship is a emerging field that combines environmental sustainability with business opportunities. This research examines green entrepreneurship mindset development for high school students at SMA YASPEN Tugu Ibu Depok. An training was conducted with 35 12th grade students to provide knowledge and shape mindsets on green business concepts and opportunities. Pre-post training surveys measured changes in perceptions. Results showed increased understanding of green entrepreneurship principles and product ideas. Participants gained creative thinking abilities to turn waste materials into economical products. Further research can expand training reach and assess real-world green business establishments by students. Fostering green entrepreneurial mindsets from early ages can propagate environmentally conscious business practices.